Implementasi Budaya Sekolah Dalam Menanamkan Karakter Peserta Didik SMP Negeri 1 Kota Serang - Ida Farida; Ria Yuni Lestari; Reza Mauldy Raharja (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The purpose of this study is to determine how the implementation of school culture in instilling the character of students of SMP Negeri 1 Kota Serang. This study uses a descriptive qualitative approach to describe the problems and focus of the study with data collection carried out through observation, interviews, and documentation. Based on the results of the study, it is known that the implementation of school culture in instilling the character of students of SMP Negeri 1 Kota Serang regarding the implementation of school culture and character instillation in the implementation of school culture of SMP Negeri 1 Kota Serang is carried out well and consistently every day which becomes a good habit of the school. The supporting and inhibiting factors that occur include adequate facilities and infrastructure but need to be improved in terms of novel reading books, the majority of students understand but there are still some students who are not yet in accordance so they must be reminded continuously, the majority of educators understand but there are still some who have not synergized so they need to remind each other among educators and the majority of parents understand and support the implementation of school culture but there are still some who are not yet in accordance so they need to be reminded continuously by educators.